Analysis of the incidence of postintubation injuries in patients intubated in the prehospital or early hospital conditions of the hospital emergency department and the intensive care unit - Cierniak M; Timler D; Sobczak R; Wieczorek A; Sekalski P; Borkowska N; Gaszynski T (Dove Medical Press, 2015)
Marcin Cierniak,1 Dariusz Timler,1 Renata Sobczak,1 Andrzej Wieczorek,2 Przemyslaw Sekalski,3 Natalia Borkowska,2 Tomasz Gaszynski1 1Department of Emergency Medicine and Disaster Medicine, Barlicki University Hospital, 2Department of Anesthesiology and Intensive Therapy, Medical University of Lodz, 3Department of Microelectronics and Computer Science, IT Centre, Lodz University of Technology, Lodz, Poland Background: Intubation is still one of the best methods to secure the airway. In the case of prehospital or early hospital conditions when factors such as urgency, stress, or inaccuracy of the undertaken activities are involved, the risk of causing complications, for instance, edema or postintubation injuries, increases, especially while dealing with a difficult intubation. The risk of improper inflation of the endotracheal tube cuff also increases, which is considered in this study.Objective: The aim of this study was to evaluate the prevalence of postintubation complications, such as postintubation injuries or edema, in a research sample, and to examine whether such complications occur more often, for example, while using a guidewire. In this study, we also evaluated the injuries associated with the inflation of the endotracheal tube cuff.Materials and methods: This study was performed on a group of 153 patients intubated in prehospital conditions. The tests were carried out in three clinical sites that received patients from prehospital care. Postintubation injuries were revealed and photographed using videolaryngoscope, such as the C-MAC and the McGrath series 5. The endotracheal tube cuff pressure was measured using a pressure gage manual (VBM Medizintechnik GmbH). The quantitative analyses of differences between incidence of variables were assessed using χ2 test for P<0.05. Analyses have been carried out using the Statistica software.Results: In the group of 153 patients, postintubation injuries occurred in 17% of cases. The dependency between using the guidewire and the occurrence of the hematomas and loss of mucosa was statistically significant (P<0.01). In nearly half (42%) of the patients the endotracheal tube cuff pressure was excessively inflated over 30 cm H2O, and in two cases, endotracheal tube displacement was observed on account of poor cuff inflation (<20 cm H2O).Conclusion: The highest percentage of overfilled cuffs were observed in the admission room. In the other wards, it was observed in 25% of cases. Even though only six cases of poor cuff inflation were noticed, the relationship between the leakage and the clinical conditions of patients is worth examining. The results would help in taking additional measures to reduce the risk of complications. Keywords: postintubation injuries, postintubation edema, endotracheal tube cuff pressure